2018
DOI: 10.1007/s11682-018-9828-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic brain activity and memory performance improvement in patients with end-stage renal disease during a single dialysis session

Abstract: Memory deficits are considered to have a great influence on self-management, dietary restriction and therapeutic regimen for end-stage renal disease (ESRD) patients with dialysis treatment. This study was aim to investigate the spontaneous brain activity and its relationship with memory performance in ESRD patients before dialysis (T1) and after 24 h (T2) during a single dialysis session. 23 ESRD patients and 25 matched healthy controls (HCs) were scanned using functional magnetic resonance imaging (fMRI) at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 44 publications
4
28
1
Order By: Relevance
“…CVLT is widely used to assess declarative verbal memory functions(Chepenik et al, 2012 ). The result of our study is identical to the result by Li et al ( 2018 ), who found that the ESRD group showed poor performance in the immediate recall total score, short-term delayed recall score, and long-term delayed recall score. Free-recall might be an important aspect of memory dysfunction in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…CVLT is widely used to assess declarative verbal memory functions(Chepenik et al, 2012 ). The result of our study is identical to the result by Li et al ( 2018 ), who found that the ESRD group showed poor performance in the immediate recall total score, short-term delayed recall score, and long-term delayed recall score. Free-recall might be an important aspect of memory dysfunction in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 91%
“…The DMN is involved in multiple brain functions including memory, visuality, and auditory attention, motor performance, and language processing (Buckner et al, 2008 ; Kim, 2012 ). Impairment of these neurocognitive areas has been found to lead to significant impairment in ESRD patients irrespective of whether they are receiving hemodialysis or peritoneal dialysis (Luo et al, 2016 ; Li et al, 2018 ). As a pivotal component of the DMN, the precuneus is closely associated with integrated tasks such as keeping wakefulness and the regulation of visual-spatial episodic memory (Buckner et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, there was a close relationship between CBF and brain metabolism, including glucose utilization, oxygen consumption, and aerobic glycolysis (Vaishnavi et al, 2010). Altered cerebral perfusion or neuronal activity in cerebral cortex was detected using only unimodal neuroimaging technique in several previous studies Peng et al, 2018). However, these results could not fully reflect their close coupling situations.…”
Section: Introductionmentioning
confidence: 65%
“…Recent studies have shown that the DMN functional alterations induced by ESRD are not limited to regional homogeneity (ReHo) (17) and amplitude of low-frequency fluctuation (ALFF) (18) changes; they are also manifested as impaired FC in independent component analysis (ICA) (19), seed-based FC analysis (20,21), and graph theory-based analysis (22,23). Most of these functional abnormalities involve the parietal lobe, PCC, Pcu, and medial frontal lobe.…”
Section: Introductionmentioning
confidence: 99%